Clinical and epidemiological data on inflammatory bowel disease, colorectal cancer and Helicobacter Pylori infection in Turkey - (:unkn) unknown (My University, 2002)
Turkey is a bridge between east and west and a midway for many emigrations. Although there is on big ethnical groups in this country, there is a great variation in culture, living conditions, dietary habits, environment, access to medical care. These factors topped by different socioeconomical conditions and genetic background lead to different epidemiology of certain diseases throughout the country. Improving hygienic conditions and socioeconomical level made the seroprevalence of Helicobacter pylori infection to decrease from 78.5% to 66.4 over the past ten years. Similar to the western epidemiological data Hp tends to affect less the young age group as compared to adults. On the other hand increasing resistance to antimicrobials used to eradicate the bacterium will obviate the need for more powerful and effective regimens in the near future. Inflammatory bowel diseases are frequently encountered in Turkey its incidence is less than North and West Europe but close to Middle East. (4.4/100.000 for UC and 2.2/ 100.000 for CD). The disease affects both sexes to the same degree. Distal Colitis in UC and ileocolitis in CD are more frequent than other lucalizations. Amebiasis occurs in about 1/3 of cases in UC and 10% of cases with CD. This parasite is observed as a concomitant infestation with IBD or as a trigger for flare up in both conditions. Colorectal cancer is the second most common GI malignancy after gastric cancer in Turkey. The distribution of colorectal cancer shows variations from west to east. Whilst esophageal and gastric cancers are more prevalent in the east, colon cancer is relatively more common in western parts of Anatolia. Males and Females seem to be affected to the same degree and the 5th and 6th decades are the more frequent ages of involvement. Although some studies reported a trend towards right sided involvement in colon cancer, rectum and sigmoid are still the sites of predilection for colon cancer. Many environmental and genetic factors play a role in the development of colon cancer but the existing small studies discussing the contribution of some etiological factors such as dietary habits, vitamin and mineral deficiencies, environment etc. have to be validated in larger, controlled trials. The common denominator of all three conditions is their strong link with some socioeconomical parameters, the threat of environmental factors, their changing incidence over the past decades and their malignant or potential malignant character which affects their prognosis. Whether it be infectious or non infectious the best would be to bring together all the existing information and to unite forces in such a direction that these disorders could be prevented or completely eradicated from the region.